The Effect Of Technology Access, Digital Literacy, And Ease Of Use On The Decision To Use The Uprintis Indonesia Platform - Andayani, Widiya Priska; Karnawati, Tin Agustina (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives:This research analyzes the influence of technology access, digital literacy, and ease of use on the decision to use the Uprintis Indonesia Platform among women’s MSMEs. Background Problems: Digital transformation presents women’s MSMEs with the challenge of the Second Level Digital Divide, where access to technology is insufficient without the ability to utilize it effectively. Novelty: The research offers novelty by integrating the Digital Divide framework and the Technology Acceptance Model (TAM) to analyze empowerment platforms within the underexplored context of Corporate Transformation 5.0. Research Methods: An associative quantitative approach was employed, utilizing a survey of 100 women’s MSMEs users of the platform in East Java. Data were analyzed through multiple linear regression. Finding/Results: Technology access, digital literacy, and ease of use each have a positive and significant influence, both individually and collectively, on usage decisions.Further analysis indicates that digital literacy is the most influential factor. Conclusion: The results reinforce the characteristics of the Second Level Digital Divide. They highlight the necessity for a strategic shift in empowerment initiatives—from solely providing technological infrastructure to enhancing digital literacy and developing genuinely user-centric platforms to promote sustained adoption.